Analisis Identitas Visual Kupat Tahu Magelang: Komunikasi, Estetika, dan Muatan Informasi dalam Membangun Citra Kuliner Daerah - Ramadhan, Ahmad Zakiy; Sunarmi, Sunarmi; Sarwanto, Sarwanto (LPPM STIKI Malang, 2025)
Visual identity plays a crucial role in shaping the image of a product, including in the local culinary industry. However, studies on how visual elements reinforce cultural identity in culinary branding remain limited. This study aims to analyze the visual identity of Kupat Tahu Magelang from the perspectives of communication, aesthetics, and information content in establishing a distinctive regional culinary identity. A descriptive qualitative approach was employed, utilizing data collection techniques such as direct observation, semi-structured interviews with business owners, and a literature review on branding and visual aesthetics. The findings indicate that the visual identity of Kupat Tahu Magelang, dominated by bold typography and striking colors, effectively captures audience attention. However, the design lacks representation of Magelang’s local cultural elements. Therefore, integrating culturally inspired visual elements, such as traditional batik motifs or culinary icons, is necessary to enhance emotional appeal and product uniqueness. This study recommends a more culture-based design strategy to strengthen the competitive advantage of Kupat Tahu Magelang in both local and national markets.